Correlation of renal function indicators and vascular damage in T2DM patients with normal renal function - Zhang, Yue-Yang; Gui, Jing; Chen, Bing-Xue; Wan, Qin (Frontiers in Endocrinology, 2023)
This study aimed to assess the correlation between renal function-related indices and vascular damages among patients with type 2 diabetes mellitus (T2DM) and normal renal function.We screened a cohort of eligible patients with T2DM, ultimately including 826 individuals. Utilizing multifactorial logistic regression, we conducted an in-depth analysis to explore the potential associations between renal function-related indices—specifically BUN, Cr, ALB, ACR, and eGFR—and the incidence of diabetic vascular damage. Additionally, to comprehensively understand the relationships, we employed Spearman correlation analysis to assess the connections between these indicators and the occurrence of vascular damage. In this cross-sectional study of 532 patients with carotid atherosclerosis (CA), the prevalence of CA was positively correlated with Cr (53.1%, 72.3%, 68.0%, P<0.05) and negatively correlated with eGFR (71.6%, 68.5%, 53.1%, P<0.05). the higher the Cr, the higher the predominance ratio of CA (T1: reference; T2:OR. 2.166,95%CI:1.454,3.225; T3:OR:1.677, 95%CI:1.075, 2.616; P<0.05), along with an eGFR of 66.9% and 52.0% in terms of sensitivity and specificity, with a 95% CI of 0.562-0.644.Within our experimental sample, a noteworthy observation emerged: Creatinine (Cr) exhibited a positive correlation with the prevalence of individuals affected by carotid atherosclerosis (CA), underscoring a potential connection between Cr levels and CA incidence. Conversely, the estimated Glomerular Filtration Rate (eGFR) demonstrated a negative correlation with the occurrence of CA, implying that lower eGFR values might be associated with an increased likelihood of CA development.